Formation of an anti-radicalism and terrorism law-aware society - Rini Fathonah; Mashuril Anwar; Maroni Maroni; Nenny Dwi Ariani (University of Merdeka Malang, 2021)
To create harmony and peace in society, every form of radicalism and terrorism must be abolished. Preventing radicalism and terrorism is not easy, because it requires a systematic and massive strategy. The role of the community is very necessary for preventing and overcoming radicalism and terrorism, for that it is important to provide understanding to the community, especially youth organizations. The activity, which was held in Batu Putuk, Teluk Betung Barat, Bandar Lampung, aims to educate and encourage the youth of Karang Taruna, Batu Putuk Village, to play an active role in preventing and overcoming radicalism and terrorism. This activity is carried out with a comprehensive method in the form of socialization, discussion, and clinical services. In line with the aim of the activity, namely educating and encouraging the youth of Karang Taruna in Batu Putuk Village to participate in efforts to prevent radicalism and terrorism, the benefits of this activity include increasing the ability of partners to recognize activities that lead to radicalism and terrorism, increasing the ability of partners to counteract the influence of radicalism and terrorism, as well as encourage the active role of partners in countering radicalism and terrorism.